Analisis Hukum Konflik Jual Beli Tanah Berdasarkan Surat Kuasa Mutlak tanpa Sepengetahuan Penjual : Studi Putusan Mahkamah Agung Nomor 680 K/Pdt/2020 - Malik Syaifuddin (Prosiding Seminar Nasional Ilmu Hukum, 2024)
This article examines the validity of the sale and purchase of land rights based on an absolute power of attorney without the knowledge of the seller, focusing on Supreme Court Decision Number 680 K/Pdt/2020. This study aims to analyze the validity of the use of an absolute power of attorney in the process of transferring land rights and its legal implications. The results of the study indicate that the use of an absolute power of attorney in the transfer of land rights is contrary to the provisions of laws and regulations, especially Article 39 paragraph (1) letter d of Government Regulation Number 24 of 1997 concerning Land Registration. This absolute power of attorney is declared null and void by law because it contains elements of irrevocable transfer of rights, which is contrary to the principle of "Nemo Plus Juris Transfere Potest Quam Ipse Habet". The court decision confirms that legal actions based on the absolute power of attorney are invalid, so the transfer of rights that occurs must be canceled. This finding emphasizes the importance of compliance with legal principles and provisions by notaries and land deed officials in the process of transferring rights to ensure legal certainty and justice.